Species relationship and genetic diversity in some Iranian Lamium L. species using ISSR markers - FATEMEH AZIMISHAD; MASOUD SHEIDAI; SAYED MEHDI TALEBI; ZAHRA NOORMOHAMMADI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Azimishad F, Sheidai M, Talebi SM, Noormohammadi Z. 2019. Species relationship and genetic diversity in some Iranian Lamium L. species using ISSR markers. Biodiversitas 20: 1963-1972. Lamium is a widespread and taxonomically complex genus of Lamiaceae which comprises of 16-38 species. This genus is represented in Iran by nine species. In the present study, we used morphological and molecular (ISSR, Cp DNA, and nrITS) data to evaluate species relationships, genetic diversity and population genetic structure of the genus. 27 morphological characteristics, including 13 qualitative and 14 quantitative, and ten ISSR markers were used for morphological and genetical evaluation of 73 accessions from eight taxa. In general, species relationships obtained from morphological and molecular data were largely congruent. In the morphological study, characteristics like the life form, leaf shape, absence/existence of bracts and shape of corolla, were distinctive traits and we did not encounter intermediate forms. Our findings indicated a very high efficiency of the ISSR markers in the identification and delimitation of Lamium species. These results confirmed the placement of L. galeobdolon in the genus Lamium and segregation of L. purpureum and L. garganicum in section Lamium. AMOVA analysis revealed that the species of this genus are genetically differentiated. Nm analysis showed very low value of gene flow among the studied species and mantel test indicated isolation by distance occurred among them.